Faktor-Faktor yang Mempengaruhi Pendapatan Tunai Usaha Ternak Babi di Kecamatan Borong Kabupaten Manggarai Timur - Tiang, Elisabeth Rivilan; Lole, Ulrikus R.; Ratu, Maria R. D. (Yayasan Sumber Daya Manusia Cerdas, 2025)
The low productivity of pigs due to farmers’ limited knowledge and skills is suspected to depress farm income. This study aims to estimate the cash income of pig farmers in Borong District, East Manggarai Regency, and to identify its determinants. The research employed a survey design involving 100 farmers across four villages. Primary and secondary data were collected over one month using structured questionnaires. The measured variables included selling price of pigs, number of pigs owned, number of pigs sold, housing and equipment costs, and health costs. Income was calculated using input–output analysis; relationships among variables were examined using correlation and multiple linear regression within a Cobb–Douglas production function framework. The results show an average cash income from pig farming of IDR 5,863,760 per year. Empirically, three factors significantly influence income: selling price (positive association), number of pigs sold (positive association), and housing and equipment costs (negative association). The model demonstrates very strong explanatory power (R² = 0.965). These findings indicate that farmers’ income is primarily shaped by price dynamics and sales volume, while efficiency in production facility costs is key to profit optimization. Practical implications include strengthening managerial and technical capacity, improving market access, and streamlining production facility costs to raise productivity and income among pig farmers in Borong.